Development and evaluation of a one-step multiplex real-time TaqMan® RT-qPCR assay for the detection and genotyping of equine G3 and G14 rotaviruses in fecal samples - Carossino, Mariano; Barrandeguy, Maria Edith; Erol, Erdal; Li, Yanqiu; Balasuriya, Udeni B.R. (BMC, 2019)
Background: Equine rotavirus A (ERVA) is the leading cause of diarrhea in neonatal foals and has a negative impact on equine breeding enterprises worldwide. Among ERVA strains infecting foals, the genotypes G3P[12] and G14P[12] are the most prevalent, while infections by strains with other genomic arrangements are infrequent. The identification of circulating strains of ERVA is critical for diagnostic and surveillance purposes, as well as to understand their molecular epidemiology. Current genotyping methods available for ERVA and rotaviruses affecting other animal species rely on Sanger sequencing and are significantly time-consuming, costly and labor intensive. Here, we developed the first one-step multiplex TaqMan® real-time reverse transcription polymerase chain reaction (RT-qPCR) assay targeting the NSP3 and VP7 genes of ERVA G3 and G14 genotypes for the rapid detection and G-typing directly from fecal specimens. Methods: A one-step multiplex TaqMan® RT-qPCR assay targeting the NSP3 and VP7 genes of ERVA G3 and G14 genotypes was designed. The analytical sensitivity was assessed using serial dilutions of in vitro transcribed RNA containing the target sequences while the analytical specificity was determined using RNA and DNA derived from a panel of group A rotaviruses along with other equine viruses and bacteria. The clinical performance of this multiplex assay was evaluated using a panel of 177 fecal samples and compared to a VP7-specific standard RT-PCR assay and Sanger sequencing. Limits of detection (LOD), sensitivity, specificity, and agreement were determined. Results: The multiplex G3 and G14 VP7 assays demonstrated high specificity and efficiency, with perfect linearity. A 100-fold difference in their analytical sensitivity was observed when compared to the singleplex assays; however, this difference did not have an impact on the clinical performance. Clinical performance of the multiplex RT-qPCR assay demonstrated that this assay had a high sensitivity/specificity for every target (100% for NSP3, > 90% for G3 VP7 and > 99% for G14 VP7, respectively) and high overall agreement (> 98%) compared to conventional RT-PCR and sequencing. Conclusions: This new multiplex RT-qPCR assay constitutes a useful, very reliable tool that could significantly aid in the rapid detection and G-typing of ERVA strains circulating in the field.